Post-Mortem Analysis of Lithium-Ion Capacitors after Accelerated Aging Tests. (January 2021) - El Ghossein, Nagham; Sari, Ali; Venet, Pascal; Genies, Sylvie; Azaïs, Philippe
Highlights: Aging mechanisms in Lithium-ion Capacitors (LiCs) strongly depend on their state of charge The growth of the Solid Electrolyte Interface (SEI) at the negative electrode increases with the increase of the state of charge Pores blocking of the positive electrode appears at very low and very high states of charge Components of the electrolyte degrade with the increase of the state of charge Storing LiCs at 3 V reduces their aging mechanisms Abstract: Lithium-ion Capacitors (LiCs) have recently emerged in the market of energy storage systems as a new technology having some of the advantages of Lithium-ion Batteries (LiBs) and Supercapacitors (SCs). As an important number of commercial LiCs combine the negative electrode of LiBs with the positive electrode of SCs, the lifetime of this new technology requires an effective analysis that can underlie degradation mechanisms related to each electrode. In order to evaluate the aging behavior of LiCs, calendar accelerated aging tests were applied to eighteen cells for twenty months in a previous study. Two temperatures, 60°C and 70°C, and three storage voltage values, 2.2 V, 3.0 V and 3.8 V were used to accelerate their aging. the The lifetime of LiCs was found to be particularly dependent on the storage voltage and the degradations of the cells were most pronounced at the highest temperature, 70°C. Therefore, in the current study, post-mortem analyses are applied to three cells that aged at different storage voltage values and 70°C. Considering the same aging mechanisms at high temperatures, only one high temperature was chosen. Two main aging mechanisms were observed: the pores blocking of activated carbon at the positive electrode and the loss of lithium ions from the negative electrode of pre-lithiated graphite. Elements responsible for these degradations were different at each voltage condition. Additional mechanisms were identified such as the degradation of the electrolyte and the decomposition of the positive current collector.